INFLUENCE OF LENGTH AND SEX OF PEPRILUS MEDIUS (PETERS) (STROMATEIDAE: PERCIFORMES), CAUGHT ON CHORRILLOS, LIMA, PERU ON ITS PARASITIC COMMUNITY - Iannacone, Jose (2008)
The aim of this work was to evaluate influence of length and sex of Pacific harvestfish Peprilus medius (Peters, 1869) (Stromateidae), a carnivore benthopelagic fish of the central coast of Peru, on its main helminths and crustacean parasites. We investigated some community components of parasitofauna of 115 P. medius necropsied between September 2007 and June 2008 from Chorrillos Fishmarket, Lima, Peru. The mean total length of fishes was 23.94.65 cm. Mean abundance of infection and mean parasite species richness was 9.23 (0-140) and 0.81 (1-3), respectively. Forty-two hosts were not parasitized (36.5 %). Infection, with 1, 2 and 3 species of parasites were 54 (47 %), 18 (15.7 %) and 1 (0.9 %), respectively. Three trematode endoparasites were found: Lecithocladium sp., Opechona bacillaris (Molin, 1859) and Lobatostoma sp. Four ectoparasites were also found: Oaxacotyle oaxacensis (Caballero & Bravo-Hollis, 1963) Levedev, 1984 (Monogenea); Caligus sp. and Bomolochus sp. (Copepoda); and Ceratothoa gaudichaudii (Milne Edwards, 1840) (Isopoda). A relationship between P. medius length and prevalence of Lobatostoma sp. was demonstrated. Seasonal differences between summer-autumn 2008 and spring 2007 infections were also shown.